Pengaruh Environmental, Social, And Governance (ESG) Terhadap Kinerja Keuangan Dengan CEO Power Sebagai Variabel Moderasi Pada Perusahaan Sektor Energy Tahun 2021-2023 - Nanang Putra Aji Pangestu; Yuyun Isbanah (Jurnal Ilmu Manajemen, 2026)
This study investigates the impact of Environmental, Social, and Governance (ESG) disclosures on the financial performance of energy sector companies in Indonesia during the 2021–2023 period, with CEO Pay Slice and CEO Tenure serving as moderating variables. The analysis uses panel-data regression with Stata 17. The findings indicate that ESG disclosures do not have a significant direct effect on Return on Assets (ROA). However, moderating effects reveal more nuanced relationships. CEO Pay Slice negatively moderates the relationship between Social Disclosure and ROA, suggesting that higher CEO compensation concentration may weaken the financial benefits of social disclosure practices. In contrast, CEO Pay Slice does not moderate the relationship between Environmental or Governance Disclosure and firm performance. Meanwhile, CEO Tenure strengthens the positive influence of Environmental Disclosure on ROA but weakens the relationship between Social Disclosure and ROA. CEO Tenure does not moderate the relationship between Governance Disclosure and financial performance. Overall, the results emphasize the importance of leadership structure and managerial incentives in shaping the effectiveness of ESG disclosures in enhancing firm performance